2003
DOI: 10.1021/bi035333y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Structural and Functional Boundaries of the Multidrug Resistance Protein 1 Cytoplasmic Loop 3

Abstract: Multidrug resistance protein (MRP) 1 is a member of the ABCC branch of the ATP binding cassette (ABC) transporter superfamily that can confer resistance to natural product chemotherapeutic drugs and transport a variety of conjugated organic anions, as well as some unconjugated compounds in a glutathione- (GSH-) dependent manner. In addition to the two tandemly repeated polytopic membrane-spanning domains (MSDs) typical of ABC transporters, MRP1 and its homologues MRP2, -3, -6, and -7 contain a third NH(2)-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
76
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 50 publications
(99 reference statements)
1
76
2
Order By: Relevance
“…MRP1 expression vectors encoding proteins lacking the first 203 amino acid residues or with mutated/chimeric COOH-terminal regions have been described previously (Grant et al, 1994;Gao et al, 1996;Qian et al, 2001a;Westlake et al, 2003Westlake et al, , 2004. Vectors for proteins that contained both modified NH 2 -and COOH-terminal regions were generated by ligation of mutant MRP1 fragments from the above-mentioned vectors into an appropriate recipient vector.…”
Section: Generation Of Mrp1 Variantsmentioning
confidence: 99%
See 4 more Smart Citations
“…MRP1 expression vectors encoding proteins lacking the first 203 amino acid residues or with mutated/chimeric COOH-terminal regions have been described previously (Grant et al, 1994;Gao et al, 1996;Qian et al, 2001a;Westlake et al, 2003Westlake et al, , 2004. Vectors for proteins that contained both modified NH 2 -and COOH-terminal regions were generated by ligation of mutant MRP1 fragments from the above-mentioned vectors into an appropriate recipient vector.…”
Section: Generation Of Mrp1 Variantsmentioning
confidence: 99%
“…Despite relatively low sequence similarity, experimental evidence and predictive hydrophobicity determinations suggest that in general, the NH 2 -terminal extensions of these proteins contain five transmembranes (TMs) and have an extracellular NH 2 terminus (Hipfner et al, 1997;Kast and Gros, 1997;Tusnady et al, 1997;Raab-Graham et al, 1999). A similar third MSD also is present in the yeast ABCC protein cadmium factor Ycf1, a probable ortholog of MRP1 (Li et al, 1996), and in other ABCC proteins identified in plants and lower eukaryotes (Tusnady et al, 1997).In MRP1, MSD0 is connected to the remainder of the protein by a cytoplasmic loop, CL3, of ϳ108 amino acids (Westlake et al, 2003). The cytoplasmic NH 2 termini of ABCC proteins lacking MSD0 show some conservation of sequence with the start of CL3 in proteins such as MRP1, suggesting that the additional MSD may have been acquired by fusion of a gene encoding a core ancestral ABCC protein with one or more genes encoding other integral membrane proteins .…”
mentioning
confidence: 99%
See 3 more Smart Citations